Geografia e arte: o uso de imagens pictóricas como possibilidade para discussão do conceito de Natureza em sala de aula - Modena, Elis (2014)
We present a study that is defined and takes place as a didactic proposal to problematize/discuss the concept of Nature in the classroom from pictorial images. For this, at first, we seek to understand and reflect on the key concepts that guide our modern view of Nature, namely: the Utilitarian, the Romantic and the Materialist. In a second moment, we seek to highlight the importance of pictorial images in understanding the concept of Nature. In fulfilling this task, we present the concept of landscape within a cultural approach and then conducted a roundup in the history of landscape painting, traversing from the Renaissance to the present day. In a third and concluding moment, the we present possibilities for the Geography teacher working with landscape paintings to discuss the concept of Nature, analyzing and considering the use of this methodology at the obstacles of learning/teaching geography in school.